HUBUNGAN TINGKAT KECUKUPAN ZAT GIZI MAKRO DAN AKTIVITAS FISIK TERHADAP STATUS GIZI ATLET BULUTANGKIS DI PEKANBARU - Asriani, Dwi Suci; Wulandari, Yulianti (Journal of Hospital Administration and Management (JHAM), 2024)
Optimal nutritional status is a crucial factor in supporting athlete performance, including badminton athletes. This study aims to analyze the relationship between macronutrient adequacy levels and physical activity on the nutritional status of badminton athletes in Pekanbaru. This research employs a quantitative approach with a cross-sectional design. The sample consists of 36 athletes selected using total sampling (saturated sample). Macronutrient adequacy levels were assessed using a three-day dietary recall, while physical activity was measured using a validated physical activity questionnaire. Nutritional status was determined based on the Body Mass Index (BMI). Data analysis using Spearman correlation test revealed a strong relationship between macronutrient adequacy levels and physical activity with the nutritional status of badminton athletes (r > 0.70; p < 0.05). The results indicate that better macronutrient adequacy and optimal physical activity contribute to improved athlete nutritional status. Therefore, ensuring sufficient macronutrient intake and maintaining a balanced level of physical activity is essential to support the nutritional status and performance of badminton athletes.